Pengaruh Subjective Norm, Attitude dan Perceived Behavioural Control terhadap Intention to Use Parkir Elektronik - Indriati Rochmah Darmayanti; Muhammad Wisnu Girindratama (Politeknik Ganesha Medan, 2021)
The purpose of this study was to determine and analyze the influence of subjective norms on the intention to use electronic parking, to find out and analyze the influence of attitudes toward intention to use electronic parking and to determine and analyze the effect of perceived behavioural control on the intention to use electronic parking. The approach used in this research is a quantitative approach. The data used are primary data with the questions that are asked in the online questionnaire, which is distributed to the population of Surabaya city residents in 2020. Respondents obtained were as many as 60 people, consisting of 27 men and 33 women. The sampling technique uses accidental sampling technique. The analysis technique used in this research is quantitative data analysis with a multiple linear regression statistical approach. In processing data, research uses warpPLS 6.0 software. The findings show that: (1) Subjective norms have a significant influence on the intention to use electronic parking (? = 0,271; p-value = 0,012). (2) Attitudes have a significant influence on the intention to use electronic parking (?= 0,293; p-value = 0,007). (3) Perceived Behavioral Control has a significant influence on the intention to use electronic parking (?= 0,503; p-value < 0,001).